Vliv rychlosti posuvu elektromagnetických indukčních měřidel na vykazovanou rychlost proudění vody - Burdová, Lenka (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Plynulý posuv měřidla bodové rychlosti vodního proudu je využíván při stanovení průtoku plošnou integrační metodou rychlostního pole. Cílem práce je experimentálně zjistit vliv rychlosti posuvu sondy elektromagnetických indukčních měřidel na stanovenou průměrnou rychlost proudění vody v příslušné svislici a horizontále.

The continuous displacement of the point velocity meter of the water current is used in the determination of the flow rate by the surface integration method of the velocity field. The aim of the work is to experimentally determine the influence of the displacement speed of the probe of electromagnetic induction meters on the determined average speed of water flow in the respective vertical and horizontal direction.
The influence of the displacement speed of electromagnetic induction meters on the reported water flow rate
Keywords: elektromagnetická indukční měřidla; rychlosti posuvu sondy; měření rychlosti proudění; měření průtoků; electromagnetic induction meters; probe displacement speeds; flow velocity measurement; flow measurement